Diseño de banco de pruebas para material aglomerado (2020)
This article shows the development of a machine that arises from the analysis of the waste of the sawing of the wood as a residual material in order to propose together with other material that would take the role of binder and in turn was a waste of another industry; for this was experimented with different wastes of which it was found that expanded polystyrene which is a residual material generated in another production process lends the appropriate properties and characteristics for the material to be proposed and jointly minimize the generation and dispersion of this particulate matter in an environment. A technical method of agglomeration and compaction was proposed to combine the residual materials mentioned above and a machine was obtained that processes a raw material that has insulation properties, as well as machining generating a possible reducing the environmental impact caused by these wastes in each of the industries where they are generated.